2018
DOI: 10.1080/00222895.2018.1474337
|View full text |Cite
|
Sign up to set email alerts
|

Force Control Characteristics for Generation and Relaxation in the Lower Limb

Abstract: We investigated the characteristics for force generation and relaxation using graded isometric contractions of the knee extensors. Participants performed the following tasks as quickly and accurately as possible. For the force generation task, force was increased from 0% to 20%, 40% and 60% of the maximal voluntary force (MVF). For the force relaxation task, force was decreased from 60% to 40%, 20% and 0%. The following parameters of the recorded force were calculated: error, time, and rate of force developmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 19 publications
2
18
0
Order By: Relevance
“…The results of the 0% task showed the onset time of relaxation from the starting level of 20% or 60% MVF to be simply 0%. This result is consistent with that of a previous study according to the basic characteristics of force generation and relaxation 7,8) , which showed that the onset time of relaxation is shorter with a large magnitude of relaxation compared to a small magnitude. The results of the 60% task indicated that it has the same characteristics as the 0% task; the onset time is shorter with a large magnitude of relaxation rather than a small magnitude in the case of consecutive movement, previous studies have focused on sequence complexity and estimated it based on the following two points: 1) overall sequence of chunks and 2) internal structure of each chunk [18][19][20][21][22][23]26) .…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…The results of the 0% task showed the onset time of relaxation from the starting level of 20% or 60% MVF to be simply 0%. This result is consistent with that of a previous study according to the basic characteristics of force generation and relaxation 7,8) , which showed that the onset time of relaxation is shorter with a large magnitude of relaxation compared to a small magnitude. The results of the 60% task indicated that it has the same characteristics as the 0% task; the onset time is shorter with a large magnitude of relaxation rather than a small magnitude in the case of consecutive movement, previous studies have focused on sequence complexity and estimated it based on the following two points: 1) overall sequence of chunks and 2) internal structure of each chunk [18][19][20][21][22][23]26) .…”
Section: Discussionsupporting
confidence: 93%
“…The result of the 0% task showed the relaxation time of the adjustment from a starting level of 20% or 60% MVF to be simply 0%. This result is consistent with that of a previous study according to the basic characteristics of force generation and relaxation 7,8) ; relaxation time is longer when the magnitude of relaxation increases. Although the results of the relaxation time in the 20%, 40%, and 60% tasks were the same as those in the 0% task, the rate of force development was significantly different.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations